2019
DOI: 10.1002/cncr.32292
|View full text |Cite
|
Sign up to set email alerts
|

Comparing surgical and nonsurgical larynx‐preserving treatments with total laryngectomy for locally advanced laryngeal cancer

Abstract: BACKGROUND:The declining 5-year overall survival (OS) of patients with laryngeal cancer has been associated with increased nonsurgical management of stage III/IV disease. To further assess this hypothesis, the authors evaluated recent OS trends and patterns of use between larynx-preserving approaches with chemoradiation (CRT) or partial laryngectomy (PL) and total laryngectomy (TL) stratified by tumor and nodal burden. METHODS: The National Cancer Data Base was used to identify 8703 patients with stage III/IV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 29 publications
(44 reference statements)
0
37
0
3
Order By: Relevance
“…In this respect, the updated guidelines of ASCO rightly recommended TL for patients with large-volume T4 and/or poor pre-treatment laryngeal functions, since such a mutilating surgical procedure has nonetheless shown to be associated with better survival and, surprisingly, even superior quality of life compared to CRT or RT alone [ 4 ]. Facing this highly heterogeneous population of advanced LCs, and the even more differentiated gamma of therapeutic options available, each with its pros and cons, the relative paucity of information about which subgroup of patients might preferably benefit from primary OP protocols vs. upfront TL is definitively worrisome [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the updated guidelines of ASCO rightly recommended TL for patients with large-volume T4 and/or poor pre-treatment laryngeal functions, since such a mutilating surgical procedure has nonetheless shown to be associated with better survival and, surprisingly, even superior quality of life compared to CRT or RT alone [ 4 ]. Facing this highly heterogeneous population of advanced LCs, and the even more differentiated gamma of therapeutic options available, each with its pros and cons, the relative paucity of information about which subgroup of patients might preferably benefit from primary OP protocols vs. upfront TL is definitively worrisome [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This topic was further addressed by Patel et al in a recent national database analysis, underling that there are no differences in survival between surgical (TL and OPHL) and non-surgical approaches (CRT) for non-T4 lesions with low nodal burden, while non-T4 tumors with high nodal burden benefit more from CRT. Nevertheless, it was pointed out that TL remains advantageous in patients with T4 LC [ 19 ]. According to these findings, adequate local control is more critical in patients with limited nodal involvement, as they have a relatively lower risk of distant metastasis, while patients with higher N categories are more exposed to distant failure.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently, however, a global trend toward therapeutic strategies aiming at organ preservation. Laryngeal neoplasm therapies are based on three main alternatives: total laryngectomy, partial laryngectomies and radiotherapy associated or not with systemic therapy 6,7 . These options are determined not only by local control of the disease but also by organ functionality.…”
Section: Larynx Hypopharynx and Tracheal Diseases And Tumorsmentioning
confidence: 99%
“…However, for certain patients, total laryngectomy must be performed, which drastically affects quality of life. Although important clinical trials have confirmed the possibility of laryngeal organ preservation in the treatment of advanced laryngeal cancer, [ 1 , 2 ] the best larynx-preservation strategy continues to be debated. [ 3 , 4 ] Here, we evaluated the efficacy of nonsurgical comprehensive treatment that sought to preserve laryngeal function for patients with advanced laryngeal carcinoma.…”
mentioning
confidence: 99%